2020
DOI: 10.3390/cancers12123503
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Burden in Meningioma Patients under a Wait-and-Watch Strategy and after Complete Resection Is High—Results of a Prospective Single Center Study

Abstract: The diagnosis of intracranial meningiomas as incidental findings is increasing by growing availability of MRI diagnostics. However, the psychological distress of patients with incidental meningiomas under a wait-and-watch strategy is unknown. Therefore, we aimed to compare the psychosocial situation of meningioma patients under wait-and-watch to patients after complete resection to bridge this gap. The inclusion criteria for the prospective monocenter study were either an incidental meningioma under a wait-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Scan-associated distress is a known phenomenon in tumor patients, causing some sort if psychological distress in majority of patients [ 1 ], although it might bring alleviation in some cases [ 26 ]. We have found that the level of distress at the follow-up visit in the same patient population as in current study was very high: the number of patients with increased values in HADS-A score is over 40% and HADS-D score over 70% at the time of the out-patient visit [ 12 ]. Contrary to expectations that the high number of distressed patients might be associated with a follow-up visit, scan-associated distress, or fear of tumor growth or relapse in this imaging, we did not find significant reduction of distress after 3 months.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Scan-associated distress is a known phenomenon in tumor patients, causing some sort if psychological distress in majority of patients [ 1 ], although it might bring alleviation in some cases [ 26 ]. We have found that the level of distress at the follow-up visit in the same patient population as in current study was very high: the number of patients with increased values in HADS-A score is over 40% and HADS-D score over 70% at the time of the out-patient visit [ 12 ]. Contrary to expectations that the high number of distressed patients might be associated with a follow-up visit, scan-associated distress, or fear of tumor growth or relapse in this imaging, we did not find significant reduction of distress after 3 months.…”
Section: Discussionmentioning
confidence: 87%
“…The patients who participated in the initial study [ 12 ] were asked to fill the questionnaires using post or telephone 3–6 months (t2) after the initial out-patient visit (t1). The telephone interview was always performed by the same interviewers (S.A.A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meningioma merupakan tumor intrakranial Loe and Maliawan (2019), angka kejadiannya mencapai 25% dari tumor intrakranial primer Hussain et al (2015). Karakteristik tumor ini adalah umumnya bersifat jinak, pertumbuhannya lambat, angka kejadiannya meningkat seiring dengan pertambahan usia sehingga sering ditemui pada pasien lanjut usia, serta lebih banyak terdiagnosis pada pasien perempuan Kalasauskas et al (2020). Berbagai kelainan neurologis fokal (hemiparesis, defisit sensorik, dan afasia) timbul akibat keberadaan tumor otak baik primer atau metastasis.…”
Section: Pendahuluanunclassified
“…Secondly, fatigue was mainly evaluated as a oncological treatment complication, thereby failing to acknowledge the primary impact of the tumor itself and other treatment-independent factors [16]. Thirdly, some studies identi ed and quanti ed fatigue in a very rudimental way, using a single-item format or as part of a general symptom inventory, and did not investigate other manifestations of fatigue [17,18]. Finally, the incidence and risk factors for multidimensional fatigue in meningioma patients have not been clearly de ned.To address these issues, we conducted the rst study, to our knowledge, of fatigue in Chinese meningioma patients newly diagnosed and ready for surgery using a multidimensional conceptualization.…”
mentioning
confidence: 99%